2003
DOI: 10.1002/ajmg.b.20043
|View full text |Cite
|
Sign up to set email alerts
|

Association of the C766T polymorphism of the low‐density lipoprotein receptor‐related protein gene with Alzheimer's disease

Abstract: The low-density lipoprotein receptor-related protein (LRP) is one of the most important cholesterol receptors in the brain. Gene variation of its ligand, apolipoprotein E, is a major genetic risk-factor for Alzheimer's disease (AD). The C-allele of the silent C766T polymorphism in exon 3 of the LRP gene might be associated with AD, however, results are conflicting and thus discussed controversially. Consequently, we compared the prevalence of this polymorphism in a homogenous cohort of patients with AD and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…Furthermore, it has been reported that different sized apo(a) isoforms differ by their interaction with low density lipoprotein receptor-related protein/· 2 macroglobulin receptor (LRP) [21]. Since LRP has been implicated in the pathogenesis of AD [22], we postulated a possible involvement of apo(a) size polymorphism in the aetiology of degenerative dementia. Furthermore, apo(a) size could directly influence the prothrombotic properties of Lp(a) by binding to fibrin in a sizedependent manner [23].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, it has been reported that different sized apo(a) isoforms differ by their interaction with low density lipoprotein receptor-related protein/· 2 macroglobulin receptor (LRP) [21]. Since LRP has been implicated in the pathogenesis of AD [22], we postulated a possible involvement of apo(a) size polymorphism in the aetiology of degenerative dementia. Furthermore, apo(a) size could directly influence the prothrombotic properties of Lp(a) by binding to fibrin in a sizedependent manner [23].…”
Section: Introductionmentioning
confidence: 94%
“…The Abeta/chaperone complexes then bind to LRP via binding sites on ApoE or alpha(2)M. Finally, clearing Abeta from the brain into the circulation by vascular transport across the BBB is mediated mainly via LRP-1 in brain microvascular endothelium. Remarkably, LRP and its ligands, ApoE and alpha2M, are all genetically associated with AD [47][48][49] . This mechanism is age dependent, and lower clearance rates in older animals correlate with decreased vascular levels of LRP [50] .…”
Section: Low-density Lipoprotein Receptor-related Proteinmentioning
confidence: 99%
“…But the results were conflicting; some studies showed that the C allele might increase the risk of SAD, while other studies found that the C allele was protective. [5][6][7] A2M is a protease inhibitor which is upregulated in the brains of patients with AD and increases degradation of the Ab peptide and inhibits b-sheet and fibril formation. 8 An association between the A2M I1000V polymorphism in exon 24 and increased risk of AD has been reported, [9][10][11] but other studies have failed to confirm these results.…”
Section: Introductionmentioning
confidence: 99%